117k views
2 votes
Expand the binomial

(x+5)^(2)

User Izak
by
6.2k points

1 Answer

0 votes

Answer:


x^(2) + 10x + 25

Explanation:

Let's first re-write the problem expression.


(x +5)^(2)  = (x+5) (x+5)

Then we apply the distributive property to get

(x + 5)(x+5) = x(x+5) + 5(x+5)

We broke up the first (x+5) to use the x and the 5 to multiply the second (x+5) element... then add them to each other (because of the + sign).


x(x+5) + 5(x+5)  = (x^(2) + 5x) + (5x + 25) = x^(2) + 10x + 25

User Massey
by
5.4k points